PENGARUH TINGKAT PENDIDIKAN DAN PENGALAMAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR PERTANAHAN KOTA TANGERANG SELATAN - Kharina Anggraeni; Liawati (Jurnal Menara, 2026)
This study aims to determine the effect of Education Level and Work Experience on Employee Performance at the Land Office of South Tangerang City, both partially and simultaneously. The method used is quantitative. The object of this research is the employees at the South Tangerang City Land Office, totaling 195 individuals. The sampling technique used is non-probability sampling, and a sample of 66 respondents was obtained using the Slovin formula. Data collection methods include observation and questionnaires. The data analysis techniques used are validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. Education Level (X1) and Work Experience (X2) have a significant effect on Employee Performance (Y), with the regression equation Y = 15.188 + 0.424X1 + 0.204X2. The correlation coefficient between the independent variables and the dependent variable is 51.8%, while the remaining 48.2% is influenced by other factors not examined in this study. The hypothesis test shows that the calculated F value is greater than the F table value (33.802 > 3.143). Therefore, it can be concluded that H0 is rejected and H1 is accepted, meaning that Education Level (X1) and Work Experience (X2) significantly affect Employee Performance (Y).